2023
DOI: 10.1523/jneurosci.0208-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Spine-Specific and Synapse-to-Nucleus Signaling by PKCδ during Plasticity

Abstract: The activity-dependent plasticity of synapses is believed to be the cellular basis of learning. These synaptic changes are mediated through the coordination of local biochemical reactions in synapses and changes in gene transcription in the nucleus to modulate neuronal circuits and behavior. The protein kinase C (PKC) family of isozymes has long been established as critical for synaptic plasticity. However, due to a lack of suitable isozyme-specific tools, the role of the novel subfamily of PKC isozymes is lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Our work thus sketches a possibly conserved role of neuronal PKCδ in the context of memory formation and consolidation in mammals, which nevertheless remains to be investigated. A possible role of PKCδ in plasticity mechanisms in mice was substantiated by the recent observation, in CA1 pyramidal neurons from mice organotypic slices, that stimulation-induced DAG production downstream of NMDA receptors (Colgan et al, 2018) can activate PKCδ in spines for local plasticity, and, at a longer timescale, its translocation to the nucleus for plasticity-induced transcription upon LTP formation (Colgan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Our work thus sketches a possibly conserved role of neuronal PKCδ in the context of memory formation and consolidation in mammals, which nevertheless remains to be investigated. A possible role of PKCδ in plasticity mechanisms in mice was substantiated by the recent observation, in CA1 pyramidal neurons from mice organotypic slices, that stimulation-induced DAG production downstream of NMDA receptors (Colgan et al, 2018) can activate PKCδ in spines for local plasticity, and, at a longer timescale, its translocation to the nucleus for plasticity-induced transcription upon LTP formation (Colgan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the activation of CREB phosphorylation at optimal calcium levels further modulates Arc transcription. While some studies have shown that nuclear calcium transients regulate CREB phosphorylation and IEG transcription (Hardingham et al, 2001; Yu et al, 2017), other studies have suggested the importance of submembrane and cytosolic calcium transients to activate other intracellular pathways to initiate IEG transcription (Deisseroth et al, 1996; Nonaka et al, 2014; Colgan et al, 2023). In this study, we focused on the nuclear calcium signaling, but the effects of the calcium transients in other parts of the neurons could also be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that PKC activity is not restricted to the stimulated spine when multiple spines are stimulated using 30-Reg (Colgan et al, 2023), which suggests that PKC could spread some distance from the stimulated loci. Additionally, TrkB has previously been shown to regulate long-distance signaling between activated synapses and the nucleus (Harward et al, 2016;Esvald et al, 2020;Moya-Alvarado and Bronfman, 2020).…”
Section: Discussionmentioning
confidence: 99%